NOD2/RIG-I Activating Inarigivir Adjuvant Enhances the Efficacy of BCG Vaccine Against Tuberculosis in Mice - Khan, Arshad; Singh, Vipul K.; Mishra, Abhishek; Soudani, Emily; Bakhru, Pearl; Singh, Christopher R.; Zhang, Dekai; Canaday, David H.; Sheri, Anjaneyulu; Padmanabhan, Seetharamaiyer; Challa, Sreerupa; Iyer, Radhakrishnan P.; et al. (Frontiers in Immunology, 2020)
Tuberculosis (TB) caused by Mycobacterium tuberculosis (MTB) kills about 1.5 million people each year and the widely used bacille Calmette-Guérin (BCG) vaccine provides a partially protection against TB in children and adults. Because BCG vaccine evades lysosomal fusion in antigen presenting cells, leading to an inefficient production of peptides and antigen presentation required to activate CD4 T cells, we sought to boost its efficacy using novel agonists of RIG-I and NOD2 as adjuvants. We recently reported that the dinucleotide SB 9200 (Inarigivir) derived from our Small molecule nucleic acid hybrid (SMNH)® platform, activated RIG-I and NOD2 showing a broad-spectrum antiviral activity against hepatitis B and C, Norovirus, RSV, influenza and parainfluenza. Inarigivir increased the ability of BCG-infected mouse APCs to secrete elevated levels of IL-12, TNF-α, and IFN-β, as well as, Caspase-1 dependent IL-1β cytokine. Inarigivir also increased the ability of macrophages to kill Mycobacterium tuberculosis in a Caspase-1-, and autophagy-dependent manner Furthermore, Inarigivir led to a Capsase-1 and NOD2- dependent increase in the ability of BCG-infected APCs to present an Ag85B-p25 epitope to CD4 T cells in vitro. Consistent with an increase in immunogenicity of BCG-infected APCs, the Inarigivir-BCG vaccine combination induced robust protection against tuberculosis in a mouse model of MTB infection, decreasing the lung burden of MTB by 1-log10 more than that afforded by BCG vaccine alone. The Inarigivir-BCG combination was also more efficacious than a muramyl-dipeptide-BCG vaccine combination against tuberculosis in mice, generating better memory T cell responses establishing it as a novel adjuvant for BCG vaccine.